Wheat heat tolerance is impaired by heightened deletions in the distal end of 4AL chromosomal arm. Issue 5 (25th January 2021) - Zhai, Huijie; Jiang, Congcong; Zhao, Yue; Yang, Shuling; Li, Yiwen; Yan, Kunfang; Wu, Shuyu; Luo, Bingke; Du, Yi; Jin, Huaibing; Liu, Xin; Zhang, Yanbin; et al.
Summary: Heat stress (HS) causes substantial damages to worldwide crop production. As a cool season crop, wheat ( Triticum aestivum ) is sensitive to HS‐induced damages. To support the genetic improvement of wheat HS tolerance (HST), we conducted fine mapping of TaHST1, a locus required for maintaining wheat vegetative and reproductive growth under elevated temperatures. TaHST1 was mapped to the distal terminus of 4AL chromosome arm using genetic populations derived from two BC6 F6 breeding lines showing tolerance (E6015‐4T) or sensitivity (E6015‐3S) to HS. The 4AL region carrying TaHST1 locus was approximately 0.949 Mbp and contained the last 19 high confidence genes of 4AL according to wheat reference genome sequence. Resequencing of E6015‐3S and E6015‐4T and haplotype analysis of 3087 worldwide wheat accessions revealed heightened deletion polymorphisms in the distal 0.949 Mbp region of 4AL, which was confirmed by the finding of frequent gene losses in this region in eight genome‐sequenced hexaploid wheat cultivars. The great majority (86.36%) of the 3087 lines displayed different degrees of nucleotide sequence deletions, with only 13.64% of them resembling E6015‐4T in this region. These deletions can impair the presence and/or function of TaHST1 and surrounding genes, thus rendering global wheat germplasm vulnerable to HS or other environmental adversities. Therefore, conscientious and urgent efforts are needed in global wheat breeding programmes to optimize the structure and function of 4AL distal terminus by ensuring the presence of TaHST1 and surrounding genes. The new information reported here will help to accelerate the ongoing global efforts in improving wheat HST.